Pengelolaan Rantai Pasok Ayam dengan Metode House of Risks - Tri Joko Wibowo; Firdanis Setyaning Handika; Ahmad Sugandhi Syah (Program Studi Teknik Industri Universitas Setia Budi, 2021)
Cil_ans Distributor is a trading business that distributes broilers from cages to traders in the Cilegon-Merak market. Some of the risks experienced by Cil_ans Distributors include: demand for chicken sizes that vary from 1.0 kg to 1.4 kg, chickens that die during distribution in a month reach 300 birds, and payment arrears. The purpose of this study is to identify the risks that arise in the chicken supply chain at Cil_ans Distributor and to determine how to mitigate the risks that arise in the chicken supply chain at Cil_ans Distributor. Risk is an event that if it occurs will have a negative impact on the achievement of performance. This study uses a House of Risk (HOR) approach in identifying, analyzing and measuring risks in the Cil_ans Distributor supply chain. The Cil_ans Distributor supply chain is modeled based on the Supply Chain Operation Reference (SCOR) method. The results identified 10 types of risk agents with ARP values ​​as follows: (A2) chicken size is uneven with ARP 1701, (A12) chickens are stressed with ARP 1512, (A20) Overheated chicken with ARP 1170, (A9) less deposit with ARP 936, (A8) increase/decrease in demand at ARP 918, (A17) overload at ARP 882, (A11) chickens brought in by consumers at ARP 792, (A10) unsold chickens at ARP 728, (A5) chickens sick with ARP 693, and (A3) less skilled employees with ARP 612. By mitigating the following risks: cover baskets with tarpaulins when distributing heavy rains, have backup DO, use paranet when distributing to customers when the weather is hot, chickens must be watered regularly every 3 hours , savings system, catching chickens is done from the largest to the smallest size, hot weather, chickens should not be caught, moving the cage, having a temporary cage to accommodate excess chickens and reminding the foreman. Keywords: ARP (Aggregate Risk Priority of agent), HOR (House of Risk), SCOR (Supply Chain Operation Reference)